Analisis Pembelajaran Matematika Menggunakan Situs Mandiri dalam Mendukung Kurikulum Merdeka di SMK Kehutanan Negeri Makassar - Suaedy, Nurdyanti; Pratiwi, Winda (Lembaga Yasin AlSys, 2024)
Background: The low results of Indonesian students in the 2022 PISA mathematics literacy survey reflect a critical gap in students' mathematical abilities, which may hinder the nation's economic progress. An independent website, developed using Google Sites, was used to teach the material, customized to align with the curriculum and essential learning outcomes. Method: A mixed-methods approach was employed, encompassing both quantitative and qualitative methods. Data collection techniques included interviews with mathematics teachers for qualitative data and questionnaires distributed to students for quantitative data. Following observations, researchers gathered information through semi-structured interviews with both students and teachers. Data validation was conducted through triangulation of sources. Results: The average percentage achieved was 88.94%, categorized as very good. It can be concluded that mathematics learning using an independent website to support the independent curriculum produced excellent results. The study indicated that mathematics learning through an independent website significantly supported the implementation of the Independent Curriculum at Makassar State Forestry Vocational School. Conclusion: The independent website is considered to support student-centered learning objectives. Teachers acknowledged that the site allows students to learn independently, at their own pace and according to their needs. Thus, mathematics learning using an independent website significantly supports the implementation of the Independent Curriculum at Makassar State Forestry Vocational School.